(untitled) (Ustozlar uchun, 2026)
This article analyzes the strategic role and professional status of bachelor-educated nurses in the modern healthcare system. The author connects personal motivations for choosing this profession with scientific and professional foundations, highlighting the transformation of nursing from a purely technical occupation into a field that requires leadership, clinical thinking, and research skills. The article also discusses the future prospects of nursing through statistical data and international experience.